ANALISIS FAKTOR YANG MEMPENGARUHI HOLDING PERIOD SAHAM BIASA PADA PERUSAHAAN GO PUBLIC YANG TERCATAT DALAM INDEX LQ45 - Vinus - Maulina; Sumiati - -; Iwan - Triyuwono (Wacana Journal of Social and Humanity Studies, 2010)
ABSTRACT The aim of this study is to know and analyze variables influencing holding period of common stock on public firm listed in LQ 45 Index, that are firms generally have good performance assessed based on both market performance and firm fundamental, then analyzing the dominance influencing variable. This study is conducted in Jakarta Stock Exchange with population of stocks listed in LQ 45 index in period of 2000 – 2001 with the total of 64 firms. The Sample Taking Method is purposive sampling with the criteria that the firms at least listed twice in LQ45 index on the study period. The Analysis method used to analyze independent variables: spread, market value, variance return, and dividend pay out ratio and dependent variable: holding period is two stage least squares multiple regression model, since there is possibility that the correlation of bid-ask spread from the current period and bid-ask spread and holding period from the previous period for every stock take place simultaneously. Results show that partially bid-ask spread variable that constitutes the different value between the highest price provided paid by buyer with the lowest price offered by seller has significance positive correlation on holding period of common stock and there is inverse correlation/significance negative between variance return variable that reflect the risk rate from stock effected by fluctuation of stock price and holding period of common stock. While, simultaneously, there is no significance correlation between dependent variable and independent variable that means bid-ask spread, market value, variance return and dividend pay out ratio can’t describe variation from holding period variable. Keywords: holding period, common stock.